Studi Literatur: Faktor yang Mempengaruhi Kejadian Stunting pada Balita - Nurafni Isrina; Eni Trisniningtyas; Naning Dianasari; Reni Mustikaningrum; Yuliati; Sri Renita Utami; Riska Dayang Safitri; Eva Rizqi Arti; Umi Bekti Iriana; Susanti Rahayu; Sofiyanti, Ida (Universitas Ngudi Waluyo, 2024)
Stunting is a chronic malnutrition disorder in toddlers and is a global health problem. The purpose of this literature review is to determine the factors that influence the incidence of stunting in toddlers. This literature review is through a search for publication results in the Google Scholar database, and the Garuda Portal between 2018-2024.The keywords used are factors AND stunting AND toddlers. Searches for articles related to 10 sources included in the inclusion criteria. The conclusion is that the factors that influence the incidence of stunting in toddlers are nutritional intake, breastfeeding, infectious diseases, parenting patterns, maternal education, economic status, family income, environmental sanitation and health services. Efforts to prevent and treat stunted toddlers need to be carried out by parents, health services and cross-sectoral. Abstrak Stunting merupakan gangguan malnuttrisi kronis pada balita dan menjadi masalah kesehatan global. Tujuan literature review ini adalah untuk mengetahui faktor-faktor yang mempengaruhi kejadian stunting pada balita. Literature review ini melalui penelusuran hasil-hasil publikasi pada database Google Scholar, dan Portal Garuda antara tahun 2018-2024. Kata kunci yang digunakan yaitu faktor-faktor dan stunting dan balita. Penelusuran artikel yang terkait 10 sumber yang termasuk dalam kriteria inklusi. Kesimpulannya bahwa faktor yang mempengaruhi kejadian stunting pada balita adalah asupan gizi, pemberian ASI, penyakit infeksi, pola asuh orang tua, pendidikan ibu, status ekonomi, pendapatan keluarga, sanitasi lingkungan dan pelayanan kesehatan. Upaya pencegahan dan penanganan balita stunting perlu dilakukan oleh orang tua, pelayanan kesehatan serta lintas sektoral.